Toxicological assessment of Chlorella vulgaris and its potential preventive effect in a chronic obstructive pulmonary disease (COPD) mouse model - Giambastiani, Lucia; Fiorentino, Sofia; Brady, Kylie; Raffaelli, Andrea; Bramanti, Emilia; Lorenzini, Erna Cecilia; Longo, Vincenzo; Sparvoli, Francesca; Pozzo, Luisa; Vornoli, Andrea (Frontiers in Toxicology, 2025)
Green microalgae, particularly Chlorella vulgaris, are a rich source of bioactive and nutritional compounds, making them promising candidates for nutraceutical applications. This study evaluated the antioxidant capacity, phenolic composition, and potential health effects of Chlorella vulgaris supplementation (1% and 8%) in male BALB/c mice over 4 weeks, as well as its preventive role in a murine model of chronic obstructive pulmonary disease (COPD). The extract showed a high antioxidant potential, supported by its phenolic and carotenoid profile. Supplementation, especially at 8%, enhanced antioxidant defences without signs of liver or kidney toxicity. In the COPD model, C. vulgaris reduced inflammation, improved oxidative stress balance, and partially restored normal lung structure. Additionally, changes in caecal metabolites suggested a positive impact on gut microbiota and metabolic homeostasis. Overall, C. vulgaris supplementation demonstrated detoxifying, antioxidant, and anti-inflammatory benefits, supporting its potential use as a functional food, particularly under stress-related conditions such as COPD.